Experimental investigation and Monte Carlo simulations of radionuclide production inside the Uranium spallation target QUINTA irradiated with a 660-MeV proton beam - Tichý, Pavel; Adam, Jindřich; Baldin, Anton Alexandrovich; Chudoba, Petr; Furman, W.; Gustov, S.A.; Khushvaktov, Jurabek; Marin, I.; Solnyshkin, Alexander A.; Suchopár, Martin; Svoboda, Josef; Tyutyunnikov, S.; et al. (EDP Sciences, 2019)
The accelerator-Driven-System (ADS) is very important to study the neutron field and radionuclide production inside simple-geometry uranium subcritical setups irradiated with high energy particle beams. A subcritical setup QUINTA was irradiated with the 660-MeV proton beam from Phasotron accelerator at the Joint Institute for Nuclear Research (JINR). The radionuclide production in the region along the beam axis was investigated by the activation technique. The aim was to compare (n,x) with (p,x) reactions using activation detectors of 59Co and natPb, and compare experimental results with the calculated results using Monte Carlo simulation code MCNPX 2.7.

The accelerator-Driven-System (ADS) is very important to study the neutron field and radionuclide production inside simple-geometry uranium subcritical setups irradiated with high energy particle beams. A subcritical setup QUINTA was irradiated with the 660-MeV proton beam from Phasotron accelerator at the Joint Institute for Nuclear Research (JINR). The radionuclide production in the region along the beam axis was investigated by the activation technique. The aim was to compare (n,x) with (p,x) reactions using activation detectors of 59Co and natPb, and compare experimental results with the calculated results using Monte Carlo simulation code MCNPX 2.7.
Experimental investigation and Monte Carlo simulations of radionuclide production inside the Uranium spallation target QUINTA irradiated with a 660-MeV proton beam
Keywords: ADS; ADS